Development of Core Entrustable Professional Activities for Iranian Pre-Graduate Dental Students: A Pilot Study : Core Entrustable Professional Activities for Dental Students - Asgari, Imaneh; Dehghani Poudeh , Mostafa; Movahedian Attar, Bijan; Hosseini Dinani, S.Mojtaba; Golkar, Parisa; Dadgostarnia, Mohammad (Journal of Dental School, 2025)
Objectives: Entrustable professional activities (EPAs) are independent tasks or responsibilities that trainees can perform once they have competence. This article presented the development of EPAs for general dentistry, focusing on oral surgery and restorative dentistry. The study aimed to create a set of EPAs that can be utilized to train and evaluate dental students in Iran. Methods: This qualitative pilot study was conducted in multiple phases. First, a focus group was formed, and their opinions were collected in three alternating rounds. After extracting the statements focusing on two fields of general dentistry curriculum, they were refined, and the importance and occurrence of the tasks were evaluated. Then, the EPA statements were categorized and validated based on the modified criteria. The EPAs were also evaluated regarding the competencies defined by the Ministry of Health of Iran and the American Dental Education Association. Results: The study identified six EPAs for general dentistry in the fields of oral surgery and restorative dentistry. These EPAs encompassed various tasks such as gathering patient information, making accurate diagnoses, developing treatment plans, performing surgical and restorative procedures, and demonstrating advanced skills in treatment implementation. The EPAs aligned with the expected competencies for a dental graduate and could serve as a framework for curriculum design, assessment planning, and tracking students’ progression. Conclusion: EPA development in general dentistry, specifically in oral surgery and restorative dentistry, offered a standardized and comprehensive approach to evaluating the competence of dental learners. By integrating EPAs into dental education, educators can ensure that students acquire the necessary abilities in independent dental practice. Although this study provided a solid foundation for implementing EPAs in dental education, further research and evaluation are necessary to assess their effectiveness and practicality.